2021
DOI: 10.1111/cge.14022
|View full text |Cite
|
Sign up to set email alerts
|

CHEDDA syndrome is an underrecognized neurodevelopmental disorder with a highly restricted ATN1 mutation spectrum

Abstract: We describe the clinical features of nine unrelated individuals with rare de novo missense or in‐frame deletions/duplications within the “HX motif” of exon 7 of ATN1. We previously proposed that individuals with such variants should be considered as being affected by the syndromic condition of congenital hypotonia, epilepsy, developmental delay, and digital anomalies (CHEDDA), distinct from dentatorubral‐pallidoluysian atrophy (DRPLA) secondary to expansion variants in exon 5 of ATN1. We confirm that the unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In addition, epilepsy, structural brain malformation, heart defect, hearing impairment, genitourinary and skeletal abnormality were also frequent among patients (Table 1 ). It was noteworthy that the insertion variant in our study, as well as three indel variants, c.3615_3176del(p.Ile1057_His1060del), c.3188_3193del(p.Leu1063_His1064del), and p.Leu1063_His1064dup, reported in CHEDDA patients in 2021 (Palmer et al, 2021 ), did not interrupt the HX arrangement but change the length of HX repeats. Therefore, both the strict arrangement and length of HX motif might be critical for ATN1 function.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…In addition, epilepsy, structural brain malformation, heart defect, hearing impairment, genitourinary and skeletal abnormality were also frequent among patients (Table 1 ). It was noteworthy that the insertion variant in our study, as well as three indel variants, c.3615_3176del(p.Ile1057_His1060del), c.3188_3193del(p.Leu1063_His1064del), and p.Leu1063_His1064dup, reported in CHEDDA patients in 2021 (Palmer et al, 2021 ), did not interrupt the HX arrangement but change the length of HX repeats. Therefore, both the strict arrangement and length of HX motif might be critical for ATN1 function.…”
Section: Resultsmentioning
confidence: 83%
“…The database included PubMed, Medline, ClinVar, and HGMD. By carefully verifying and avoiding the duplication of cases, we finally found 4 articles including 17 cases with CHEDDA and 15 variants, including 10 missense mutations and 5 indels (Figure 1b ) (Hui et al, 2020 ; Mosca et al, 2007 ; Palmer et al, 2019 , 2021 ). By comparing the clinical manifestations of all CHEDDA patients, we found that all patients presented infantile hypotonia, global developmental delay, and dysmorphic facial features.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations